Колдовская вода: повесть / Леонид Влодавец ; [художники А. Яцкевич, Л. Рябинин] - Влодавец Леонид Игоревич (Страшилки, 2002)
Экземпляры: Ф28 (20191204) / Инвентарный номер: 58700 / Цена: 20.00 / Сис.шифр: Р2ср / Авт.знак: В 58 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6